Is there still a role for two-phase contrast-enhanced CT and virtual monoenergetic images in the era of photon-counting detector CT? - Estler, Arne; Nikolaou, Konstantin; Schönberg, Stefan; Bamberg, Fabian; Froelich, Matthias F.; Tollens, Fabian; Verloh, Niklas; Weiss, Jakob; Horger, Marius; Hagen, Florian (Diagnostics, 2023)
Background: To compare the diagnostic characteristics between arterial phase imaging versus portal venous phase imaging, applying polychromatic T3D images and low keV virtual monochromatic images using a 1st generation photon-counting CT detector, of CT in patients with hepatocellular carcinoma (HCC). Methods: Consecutive patients with HCC, with a clinical indication for CT imaging, were prospectively enrolled. Virtual monoenergetic images (VMI) were reconstructed at 40 to 70 keV for the PCD-CT. Two independent, blinded radiologists counted all hepatic lesions and quantified their size. The lesion-to-background ratio was quantified for both phases. SNR and CNR were determined for T3D and low VMI images; non-parametric statistics were used. Results: Among 49 oncologic patients (mean age 66.9 ± 11.2 years, eight females), HCC was detected in both arterial and portal venous scans. The signal-to-noise ratio, the CNR liver-to-muscle, the CNR tumor-to-liver, and CNR tumor-to-muscle were 6.58 ± 2.86, 1.40 ± 0.42, 1.13 ± 0.49, and 1.53 ± 0.76 in the arterial phase and 5.93 ± 2.97, 1.73 ± 0.38, 0.79 ± 0.30, and 1.36 ± 0.60 in the portal venous phase with PCD-CT, respectively. There was no significant difference in SNR between the arterial and portal venous phases, including between “T3D” and low keV images (p > 0.05). CNRtumor-to-liver differed significantly between arterial and portal venous contrast phases (p < 0.005) for both “T3D” and all reconstructed keV levels. CNRliver-to-muscle and CNRtumor-to-muscle did not differ in either the arterial or portal venous contrast phases. CNRtumor-to-liver increased in the arterial contrast phase with lower keV in addition to SD. In the portal venous contrast phase, CNRtumor-to-liver decreased with lower keV; whereas, CNRtumor-to-muscle increased with lower keV in both arterial and portal venous contrast phases. CTDI and DLP mean values for the arterial upper abdomen phase were 9.03 ± 3.59 and 275 ± 133, respectively. CTDI and DLP mean values for the abdominal portal venous phase were 8.75 ± 2.99 and 448 ± 157 with PCD-CT, respectively. No statistically significant differences were found concerning the inter-reader agreement for any of the (calculated) keV levels in either the arterial or portal-venous contrast phases. Conclusions: The arterial contrast phase imaging provides higher lesion-to-background ratios of HCC lesions using a PCD-CT; especially, at 40 keV. However, the difference was not subjectively perceived as significant.
Gesehen am 13.06.2023